The criterion validity of a newly developed Ballroom Aerobic Test (BAT) protocol against objective methods - Despot, T.; Plavec, D. (Sports, 2025)
Although laboratory testing to assess aerobic capacity has been a `gold standard` in sports science, its high costs and time-consuming protocols may not be feasible for monitoring and tracking progress in limited conditions. In dancesport athletes, several field-based aerobic tests have been proposed, but the majority of them have been developed for ballet or contemporary dancers at the individual level, while the data among dance couples engaging in standard dance styles is lacking. Therefore, the main purpose of this study was to validate a newly developed Ballroom Aerobic Test (BAT) protocol against objective methods. Twelve standard dancesport couples (age: 20.4 ± 3.9 years; height: 172.1 ± 8.7 cm; weight: 60.1 ± 9.4 kg) with 8.2 ± 3.4 years of training and competing experience participated in this study. Ventilatory and metabolic parameters were generated using the MetaMax® 3B portable gas analyzer (the BAT), while the KF1 (an increase in speed by 0.5 km * h-1 by every minute) and Bruce protocols were followed in laboratory-based settings on the running ergometer. Large to very large correlations were obtained between the BAT and KF1/Bruce protocols for the absolute maximal oxygen uptake (VO2max; r = 0.88 and 0.87) and relative VO2max (r = 0.88 and 0.85), respiratory exchange ratio (RER; r = 0.78 and 0.76), expiratory ventilation (VE; r = 0.86 and 0.79), tidal volume (VT; r = 0.75; 95% CI = 0.57-0.87; p < 0.001), ventilatory equivalent for O2 (VE/VO2; r = 0.81 and 0.80) and CO2 (VE/VCO2; r = 0.78 and 0.82), and dead space (VD/VT; r = 0.70 and 0.74). The Bland-Altman plots indicated no systematic and proportional biases between the BAT and KF1 protocols (standard error of estimate; SEE = ± 3.36 mL * kg-1 * min-1) and the BAT and Bruce protocols (SEE = ± 3.75 mL * kg-1 * min-1). This study shows that the BAT exhibits satisfactory agreement properties against objective methods and is a valid dance protocol to accurately estimate aerobic capacity in dancesport athletes participating in standard dance styles.